Hyperleptinemia as a Prognostic Factor for Preeclampsia: a Cohort Study - Hugo Mendieta Zerón; Verónica Jackeline García Solorio; Pamela Montserrat Nava Díaz; Adriana Garduño Alanís; Jonnathan Guadalupe Santillán Benítez; Victoria Domínguez García; Carolina Escobar Briones; Edgar Denova Gutiérrez (Acta Medica, 2012)
Introduction: Leptin is an adipokine which has a direct relationship to obesity. Our aim was to measure this hormone in pregnant women at three months intervals throughout their pregnancies to determine the serum value of those who developed preeclampsia. Material and Methods: We followed 19 women (median age 24.8 ± 5.7 years) with pre-gestational Body Mass Index (BMI) less than 25 kg/m2, 21 (median age 26.1 ± 4.6 years) with BMI higher than 25 kg/m2 and 16 (median age 30.9 ± 5.8 years) with Gestational Diabetes Mellitus (GDM) (median age 30.9 ± 5.8 years), recruited in the 1st trimester of pregnancy. Serum levels of leptin were measured with radioimmunoassay (RIA) technique. Results: In the first trimester of pregnancy leptin levels showed statistically significant differences between normal weight and overweight-obese women (p 2 and leptin ≥ 40 ng/ml in the second trimester, the Odds Ratio (OR) to develop preeclampsia was of 47.95% CI (4.1–527.2). Analyzing leptin values with ROC curves, the greatest area under the curve (AUC) was for leptin in the second trimester (0.773, CI: 0.634–0.911). Conclusion: Women with morbid obesity (BMI ≥ 40 kg/m2) had significantly higher levels of serum leptin (p < 0.01) and a value of 40 ng/ml of this hormone seems to be predictive of developing preeclampsia in this group of patients.